Estudo dos parâmetros cinéticos da pirólise do sabugo de milho, palha de soja e caroço de açaí - Menoncin, Thiago Henrique (2024)
Environmental concerns related to the use of fossil fuels have driven countries to seek renewable energy alternatives to sustainably meet energy demands. In this context, waste from agricultural and industrial sectors, which typically have no economic value, can be transformed into significant energy sources. One way to utilize this waste is through pyrolysis, a process that thermochemically converts materials. This conversion results in gases, liquids, and/or solids that can be used as energy sources or as raw materials for agriculture. To increase the efficiency of pyrolysis reactors, it is necessary to understand the physicochemical characteristics, thermal behavior, and kinetic parameters of the reactions involved. Therefore, the objective of this study was to evaluate the kinetic parameters (activation energy, pre-exponential factor, and reaction model) of the pyrolysis process of açaí seed, corn cob, and soybean straw, as well as to analyze the physicochemical and thermal properties of these biomasses. The physicochemical characterization was performed through proximate analysis, elemental analysis, calorific value calculation, and analysis of individual components. Thermogravimetry was conducted in an inert nitrogen atmosphere, with temperatures ranging from 30°C to 900 °C, using four heating rates: 5, 10, 15, and 20 °C.min-1 for the different biomasses. The determination of kinetic parameters was performed using non-isothermal isoconversional methods: Flynn-Wall-Ozawa (FWO), Friedman, modified Coats-Redfern (CRM), and Kissinger. In thermal analysis, the pyrolysis of the biomasses occurred rapidly. The main mass loss of açaí seed occurred between 240 and 484 °C, corn cob between 260 and 437 °C, and soybean straw between 231 and 473 °C. The results obtained for the average activation energy (Ea) of the pyrolysis of açaí seed, corn cob, and soybean straw were, respectively, for the FWO model: 216.76, 173.68, and 215 kJ.mol-1; for the Friedman model: 229.74, 179.65, and 227.27 kJ.mol-1; for the CRM model: 218.05, 172.77, and 216.15 kJ.mol-1; and for the Kissinger model: 173.42, 161.29, and 161.16 kJ.mol-1. In mathematical simulations, the FWO method provided the best overall fit for the three biomasses. The results demonstrate how the decomposition behavior and its kinetic parameters are influenced by the biomass type and the heating rate of the process.